A Descriptive Analysis of English - Indonesian Code Switching by Teachers of Paud Cipta Kreatif Bangsa Palembang - Gaya Tridinanti (Jurnal Didascein Bahasa, 2016)
ABSTRACT: The objective of this study was to find out the reason of English teachers switch their language during teaching process and the types of code switching were used by them in teaching learning process in PAUD Cipta Kreatif Bangsa Palembang. The population of this study was English teacher at PAUD Cipta Kreatif Bangsa 2015, the number of teacher are eight. The Sample was used in this study just one teacher. The Method of this study is descriptive qualitative method. Technique for collecting the data by observation and interview. Based on this study, the writer found that there are three types of code switching that is used by teacher in the classroom, they are : 1) extra – sentential code switching, 2) inter – sentential code switching, and 3) intra – sentential code switching. The writer also found some reasons why teacher switch their language, they are : (1) To clarify expalanation, (2) To show their formality to the students when they speak in the, (3) To talk about a particular topic a teacher feels free and more comfortable to express their emotions, excitements in the classroom, and (4) For affective functions, teacher switches code to express his/her emotional feeling, and the students do not have to understand the meaning but can receive the affective meaning of the speaker whether he/she is happy, excited, sad, angry, mocking the hearer, and so on. Key words: code switching, descriptive qualitative.